2008
DOI: 10.1080/14017430701652282
|View full text |Cite
|
Sign up to set email alerts
|

Signal-averaged P wave duration and the long-term risk of permanent atrial fibrillation

Abstract: Prolonged SAPWD (a marker of atrial remodelling) appears to be a risk factor for long-term development of permanent AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Thus, IAB (partial or advanced) has been found to be associated with new-onset AF in patients from a general hospital population, 21 , recurrence of AF postelectrical or pharmacological cardioversion, 22,23 , AF recurrence after pulmonary vein isolation, 24 and progression of paroxysmal AF to the persistent or permanent forms of the disease. 25,26 In patients with CHF, the association of Pwave abnormalities with development of AF was first described by Yamada et al 15 using signal averaged ECG (SAECG). They reported abnormal P-wave duration by SAECG in 38% of patients at baseline and higher incidence of paroxysmal AF in subjects with rather than without abnormal P-wave duration during the follow-up (32% vs 2%; P = 0.0002).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IAB (partial or advanced) has been found to be associated with new-onset AF in patients from a general hospital population, 21 , recurrence of AF postelectrical or pharmacological cardioversion, 22,23 , AF recurrence after pulmonary vein isolation, 24 and progression of paroxysmal AF to the persistent or permanent forms of the disease. 25,26 In patients with CHF, the association of Pwave abnormalities with development of AF was first described by Yamada et al 15 using signal averaged ECG (SAECG). They reported abnormal P-wave duration by SAECG in 38% of patients at baseline and higher incidence of paroxysmal AF in subjects with rather than without abnormal P-wave duration during the follow-up (32% vs 2%; P = 0.0002).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no difference in mean PWD between the healthy controls and the inflammatory arthritis cohort. The signal‐averaged PWD is a well‐validated method that can be used to predict AF development . In patients diagnosed with paroxysmal AF, PWD is significantly longer as compared to healthy control patients, and is a marker of the adverse electromechanical remodeling within the atria of AF patients, with marked changes in PWD yielding high risk of AF development .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] A study by Bayes, et al found that, during a 30-month follow-up of 16 patients with IAB, half developed AF. 7) In an investigation by Agarwal, et al, 308 patients developed AF during a mean of 16 months, and 52% had IAB.…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the findings of previous studies that IAB was associated with an increased risk of AF. [7][8][9][10][11] Patients meeting these criteria should also be followed for new onset AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation